Parallel decrease of tissue factor surface exposure and increase of tissue factor microparticle release by the n-3 fatty acid docosahexaenoate in endothelial cells - Del Turco, Serena; Basta, Giuseppina; Lazzerini, Guido; Evangelista, Monica; Rainaldi, Giuseppe; Tanganelli, Piero; Camera, Marina; Tremoli, Elena; De Caterina, Raffaele (Thrombosis and haemostasis, 2007)
Tissue factor (TF) is expressed on the endothelium in response to inflammatory mediators, giving endothelial cells a pro-thrombotic phenotype. Since fish-derived n-3 fatty acids (FA) have been associated with reduced incidence of myocardial infarction, we investigated the endothelial effects of the most abundant n-3 FA, docosahexaenoate (DHA), on TF expression. Human umbilical vein endothelial cells were pre-incubated with DHA (or stearate and arachidonate as controls) for 48-72 hours, and then stimulated with bacterial lipopolysaccharide (LPS) or tumor necrosis factor-alpha. Pre-incubation of endothelial cells with DHA (but not stearate or arachidonate) concentration-dependently reduced surface protein exposure, independent of TF mRNA or total protein expression regulation. Conversely, DHA treatment in conjunction with activating stimuli, induced the release of endothelial TF-exposing microparticles from endothelial cells, quantitatively accounting for the decreased TF cell surface exposure. In conclusion, DHA treatment, with a time-course consistent with its incorporation in membrane phospholipids, increases the release of TF-exposing microparticles from endothelial cells, accounting for decreased endothelial cell TF surface exposure, thus potentially modifying the overall endothelial control of microparticle-related effects.